Critical Infrastructure - Jamie Allen (A Peer-Reviewed Journal About, 2014)
The essay and ideas included here is a discussion of the topics raised through CRITICAL INFRASTRUCTURE, an artistic research and production residency that took place as part of the lead up to the transmediale festival, afterglow, 2014. The project’s initiation was about uncovering the resources and reserves of physical and material energies, signals and data that scaffold the very possibility of post-digital art-and-technology practices. Through a series of public workshops, and an installation project situated within the transmediale 2014 festival, CRITICAL INFRASTRUCTURE’s ‘post-digitality’ is not only historical-temporal, but immediate, and dredged up from below, in the present. The artistic project stemming from research and public events through the project creates a media-archaeological site-survey, revealing data and depth of the present moment of an art and technology festival.